Size-Fractionated Biogenic Silica Standing Stocks and Carbon Biomass in the Western Tropical North Pacific: Evidence for the Ecological Importance of Pico-Sized Plankton in Oligotrophic Gyres - Wei, Yuqiu; Zhang, Zhaoyi; Cui, Zhengguo; Sun, Jun (Frontiers in Marine Science, 2021)
Biogenic silica (bSi) standing stocks and carbon (C) biomass of small plankton are rarely studied together in previous analyses, especially in oligotrophic gyres. Within the oligotrophic western tropical North Pacific, based on size-fractionated bSi and biovolume-derived C analyses in three size fractions (i.e., 0.2-2 µm; 2-20 µm; >20 µm), we observed that picophytoplankton (<2 μm) contributed a measurable and significant proportion of both bSi standing stocks and C biomass. The estimated contributions of pico-sized fraction to total bSi standing stocks and living C biomass averaged 66% and 49%, respectively, indicating the ecological importance of small plankton in the Si and C cycles in oligotrophic areas. In contrast, the average contributions of large diatoms (i.e., cells>2 μm) to total bSi standing stocks and living C biomass were 9% and 16%, respectively, suggesting that the role of diatoms in marine Si and C cycles may have been overestimated in previous analyses. Due to the overwhelming predominance of picocyanobacteria in the oligotrophic western tropical North Pacific, their contributions to total bSi stocks and C biomass were quantitatively important and accounted for more of the bSi and C associated with living cells than did diatoms. In addition, water temperature and light intensity were likely the key determinants of the variations in size-fractionated bSi standing stocks and living C biomass, but not nutrient availability. Collectively, these findings encourage a reconsideration of the previously underestimated role of small plankton in understanding the Si and C cycles in the ocean, and may provide insights into the interpretations of disproportionate budgets of Si and C in oligotrophic oceans.